Versatile, facile and low-cost single-cell isolation, culture and sequencing by optical tweezer-assisted pool-screening. Issue 1 (7th December 2022) - Xu, Teng; Li, Yuandong; Han, Xiao; Kan, Lingyan; Ren, Jing; Sun, Luyang; Diao, Zhidian; Ji, Yuetong; Zhu, Pengfei; Xu, Jian; Ma, Bo
Abstract : An optical tweezer-assisted pool-screening and single-cell isolation system is established for precise, indexed isolation of individual cells, with features of versatility, facileness, flexibility, modularized design, and low cost. Abstract : Real-time image-based sorting of target cells in a precisely indexed manner is desirable for sequencing or cultivating individual human or microbial cells directly from clinical or environmental samples; however, the versatility of existing methods is limited as they are usually not broadly applicable to all cell sizes. Here, an optical tweezer-assisted pool-screening and single-cell isolation (OPSI) system is established for precise, indexed isolation of individual bacterial, yeast or human-cancer cells. A controllable static flow field that acts as a cell pool is achieved in a microfluidics chip, to enable precise and ready screening of cells of 1 to 40 μm in size by bright-field, fluorescence, or Raman imaging. The target cell is then captured by a 1064 nm optical tweezer and deposited as one-cell-harboring nanoliter microdroplets in a one-cell-one-tube manner. For bacterial, yeast and human cells, OPSI achieves a >99.7% target-cell sorting purity and a 10-fold elevated speed of 10–20 cells per min. Moreover, OPSI-based one-cell RNA-seq of human cancer cells yields high quality and reproducible single-cell transcriptome profiles. The versatility, facileness, flexibility, modularized design, and low cost of OPSI suggest its broad applications for image-based sorting of target cells.